Decision making analysis for the business allocation in the northern border of Mexico - Reyes-Madrigal, Arturo (Universidad Autónoma de Tamaulipas, 2009)
The objective of this research is to formulate a model to explain how the decision making process for the location of the business and the factors that make the competitive edge of the border northeast of Mexico. Identify the variables that significantly influence decision making and quantify the degree of influence of these variables in the process. The solution of the above, the following can result in benefits, such as identifying the major difficulties affecting the owners or those responsible for effective business decisions on the  location of business. A study of field surveys by the maquiladoras and carriers of the border northeast of Mexico. We obtained a sample of 150 valid observations, and used statistical techniques, test t, analysis of variance (Anova) and cross tabulations to identify significant variables in the analysis. The most important contribution in this research is the proposed model, providing a structure for planning the future location of sites and serve the best senior management to manage this process. In this research, based on the opinion of respondents, the location of corporate strategic factors are the same for the maquiladoras and carriers. If there is knowledge of the determinants of competitive advantage, by each of the municipalities in the northeastern border of Mexico, will develop an environment conducive to the establishment of new businesses and the relocation of existing ones, thereby allowing the attraction of capital investors and hence the generation of jobs.